MODERN TECHNOLOGICAL APPROACHES TO IMPROVING PHYSICAL QUALITIES IN THE SPORTS-EDUCATION PROCESS - Turguntoshev Muxlisbek Ilhomjon ogli (Web of Journals Publishing, 2025)
This article analyzes the role of modern technologies in developing physical qualities (strength, speed, endurance, flexibility, and coordination) and methods of their application. The research discusses the importance of sensor technologies, virtual and augmented reality (VR/AR), artificial intelligence, and mobile applications in improving and monitoring physical fitness. The results demonstrate the potential of modern technologies to enhance the effectiveness of physical exercises, provide personalized approaches, and strengthen motivation. Additionally, the current limitations and future prospects of applying technologies in sports and physical education are discussed.
Keywords: Physical qualities, modern technologies, sensors, VR/AR, artificial intelligence, personalized training, motivation.